2014
DOI: 10.11118/actaun201159030111
|View full text |Cite
|
Sign up to set email alerts
|

Effect of genotype, sex and litter size on growth and basic traits of carcass quality of light lambs

Abstract: KUCHTÍK, J., DOBEŠ, I., HEGEDÜŠOVÁ, Z.: Eff ect of genotype, sex and litter size on growth and basic traits of carcass quality of light lambs. Acta univ. agric. et silvic. Mendel. Brun., 2011, LIX, No. 3, pp. 111-116 Evaluation of the eff ect of genotype (Romanov breed: n = 26, and F1 crossbreds of Suff olk-Romanov: n = 29), sex (males: n = 37 and females: n = 18) and litter size (singles: n = 6, twins: n = 16, triples: n = 21 and quadruplets: n = 12) on growth and basic carcass quality traits of light lamb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…DG 100 by 1.79 kg higher, respectively 17.22 g higher compared to ewe -lambs (P < 0.01). These results are in opposite with Kuchtík et al (2010), Kuchtík et al (2011) who found no signifi cant eff ect on growth between sexes, although they confi rm higher daily gains by males. The level of DG 100 defi ned in the breed standard for Texel is 250 g per day for ram and for ewe -lambs 200 g per day -thus, in both cases the results in the monitored herd were exceeded by 5.39 g per day in rams, respectively 38.17 g per day in ewes.…”
Section: Eff Ect Of Lambs' Gendercontrasting
confidence: 65%
“…DG 100 by 1.79 kg higher, respectively 17.22 g higher compared to ewe -lambs (P < 0.01). These results are in opposite with Kuchtík et al (2010), Kuchtík et al (2011) who found no signifi cant eff ect on growth between sexes, although they confi rm higher daily gains by males. The level of DG 100 defi ned in the breed standard for Texel is 250 g per day for ram and for ewe -lambs 200 g per day -thus, in both cases the results in the monitored herd were exceeded by 5.39 g per day in rams, respectively 38.17 g per day in ewes.…”
Section: Eff Ect Of Lambs' Gendercontrasting
confidence: 65%
“…Regarding the carcass traits (Tab. II), the gender did not have significant effect on dressing percentage (DP), while its slightly higher value was found in MLs, which is in accordance with Kuchtík et al (2011). In contrast, Rosa et al (2007) found in both genders of the Romney Marsh lambs a higher DP compared to findings of the present study.…”
Section: Resultssupporting
confidence: 70%
“…With regard to carcass traits, in FLs is often recorded the higher dressing percentage (DP) and fatness compared to MLs (Cividini et al, 2005;Rodríguez et al, 2008). However, Kuchtík et al (2011) found only slightly higher DP in MLs.…”
Section: Introductionmentioning
confidence: 99%
“…Meat parameters and meat quality are annually recorded by the Association of Sheep and Goat Breeders. Kuchtík et al (2010Kuchtík et al ( , 2011, P t á č e k et al (2011), and Š t o l c et al (2011). In the present study we investigated the effects of year and month of lambing, gender of lamb, bloodline of Sire, age of ewe and litter size in the meat-type sheep Charollais and combined-type (wool-meat) sheep Kent.…”
Section: Introductionmentioning
confidence: 99%